2017
DOI: 10.1200/jco.2017.35.15_suppl.2584
|View full text |Cite
|
Sign up to set email alerts
|

First-in-human phase 1 study of ETC-159 an oral PORCN inhbitor in patients with advanced solid tumours.

Abstract: 2584 Background: The Wnt signalling pathway is involved in cellular proliferation, differentiation, migration and implicated in stem cell function in several cancers. ETC-159 is a selective small molecule inhibitor of porcupine, an enzyme required for palmitoylation and secretion of all Wnt ligands. In preclinical studies, ETC-159 induced tumour regression in patient-derived xenograft models. Methods: Open-label, multi-centre study to determine safety, maximum tolerated dose, pharmacokinetics, pharmacodynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…It was also reported that long-term exposure to a PORCN inhibitor in vitro selected for a AXIN1-mutant clone in a RSPO3-translocated colorectal cancer cell line and the AXIN1 mutation drove acquired resistance to the PORCN inhibitor [20]. Moreover, on-target adverse effects of Wnt pathway blockade by PORCN inhibitors, including bone loss and dysgeusia, were observed in a preclinical study and clinical trials [21][22][23]. One strategy to overcome drug resistance and reduce adverse effects is synergistic drug combinations, through which lower drug doses can be used to achieve improved anticancer efficacy.…”
Section: Introductionmentioning
confidence: 96%
“…It was also reported that long-term exposure to a PORCN inhibitor in vitro selected for a AXIN1-mutant clone in a RSPO3-translocated colorectal cancer cell line and the AXIN1 mutation drove acquired resistance to the PORCN inhibitor [20]. Moreover, on-target adverse effects of Wnt pathway blockade by PORCN inhibitors, including bone loss and dysgeusia, were observed in a preclinical study and clinical trials [21][22][23]. One strategy to overcome drug resistance and reduce adverse effects is synergistic drug combinations, through which lower drug doses can be used to achieve improved anticancer efficacy.…”
Section: Introductionmentioning
confidence: 96%
“…For example, we and others found that daily oral doses of PORCN inhibitors that gave 95% tumor growth inhibition in mouse xenograft models produced no discernable effect on the intestinal epithelium (Madan et al, 2016;Proffitt et al, 2013;Liu et al, 2013). Moreover, the PORCN inhibitor ETC-159 is also well tolerated in humans in phase I clinical trials (Teneggi et al, 2016;Ng et al, 2017). As recent studies indicate that subepithelial myofibroblasts, rather than the intestinal epithelium, are an important source of Wnts and Wnt agonists in the gut essential for intestinal homeostasis (Kabiri et al, 2014;Greicius et al, 2018), here we tested if these myofibroblasts, and more broadly, intestinal stromal cells, are intrinsically drug resistant.…”
Section: Introductionmentioning
confidence: 97%
“…The authors start by investigating a surprising discrepancy: shutting down Wnt ligand secretion through PORCN inhibition or genetic knockout in purely epithelial ''mini-guts'' (organoids) leads to complete disruption of the stem cell niche. In striking contrast, mice treated with comparable doses of PORCN inhibitors display negligible gut toxicity (Madan et al, 2016), and an early-stage clinical trial corroborates these findings in hu-mans (Ng et al, 2017). The authors propose that the explanation for this is found in the myofibroblasts, as the sensitivity of epithelial organoids to PORCN inhibition was reduced when they were co-cultured with myofibroblasts.…”
mentioning
confidence: 77%